EXCITATION OF VUV EMISSIONS IN THE REGION SHORTER THAN 130 NM BY ELECTRON COLLISIONS WITH GLYCINE MOLECULES - Bohachov, H.G. (Reports of the National Academy of Sciences of Ukraine, 2024)
An experimental setup modemized for the study of VUV radiation arising from the interaction of slow electrons with amino acid molecules is described. A three-anode electron gun with a ribbon oxide cathode was used to produce a rectangular electron beam. The beam current density in the energy range of 10—300 eV was ~10–3 A/cm2 with electron energy inhomogeneity of ~1.5—2.5 eV. A beam of molecules was obtained by the effusion method by resistive heating of the substance under investigation in a chamber with an effusion channel Ø 0.8 mm long by 3 mm. The beams were intersected at right angle and the emission from the area of beam intersection in the mutually perpendicular direction was analysed by a VUV monochromator assembled according to the Seiya-Namioka scheme based on a concave spherical grating (Rm = 500 mm, 1200 line/mm). A secondary electron multiplier with trough-shaped dynodes was used as a detector of VUV radiation. The sensitivity range of the monochromatordetector system was limited to the range 80—130 nm. The experiment provided two types of data: first, the spectral composition of radiation from the collision zone of beams at fixed values of electron energy; second, the excitation functions of individual emissions, that is, the dependence of intensity on electron energy per unit current. In both cases, the measurement process was carried out with using an automated data collection acquisition system based on an IBM-compatible PC with the use of HOLIT Data Systems expansion boards — digital input-output and digital-to-analog converter. The described setup investigated the emission spectrum in the 80—130 nm region induced by collisions of electrons with glycine molecules at electron energies in the 25—300 eV region. It was found that the spectrum consists mainly of the lines of the hydrogen atom - the Lyman series. For the most intense line at 121.6 nm, the H I resonance line, the excitation function was measured for the first time and the excitation threshold was determined to be 20 ± 1.5 eV. The presence of hydrogen atom lines in the emission spectrum is associated with the process of ionization/fragmentation with the release of excited hydrogen atoms.